Analisis kausalitas antara pengeluaran pemerintah dan pertumbuhan ekonomi di Pulau Sumatera - Nadine Brillianta Hanifah; Syamsurijal A Kadir; Anna Yulianita (Jurnal Ekonomi Pembangunan, 2017)
This study aims to investigate the relationship between government expenditure and economic growth in each province on the island of Sumatra during the period 2007-2016 using panel data. The method used is a quantitative approach by applying the Granger Causality model. The findings of this study indicate that there are no two-way relationships from the 10 provinces in Sumatra. But there is a one-way relationship between government spending and economic growth, which is found in the Province of West Sumatra and Bengkulu Province. Whereas the other 8 provinces have no one-way and two-way causality relationship